Solid electrolytic capacitor and method of manufacturing same

JP7636707B2Active Publication Date: 2025-02-27NIPPON CHEMI CON CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020063757
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-03-31
Publication Date
2025-02-27
Estimated Expiration
2040-03-31

AI Technical Summary

Benefits of technology

【0018】 本発明によれば、引出端子により生じた欠陥部付近に導電性高分子が存在する確率が少なくなるので漏れ電流を抑制することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007636707000004
    Figure 0007636707000004
  • Figure 0007636707000005
    Figure 0007636707000005
  • Figure 0007636707000006
    Figure 0007636707000006
Patent Text Reader

Abstract

To provide a solid electrolytic capacitor with a reduced leakage current.SOLUTION: A solid electrolytic capacitor includes an anode foil 3 on which a dielectric oxide film is formed, a drawer terminal 6-1 connected to the anode foil 3, a capacitor element 2 including the anode foil 3, and a solid electrolyte formed in the capacitor element and containing a conductive polymer. A coating layer 14 that repels a conductive polymer-forming solution is formed between the anode foil 3 and the drawer terminal 6-1. Further, preferably, the coating layer 14 is formed on the drawer terminal 6-1 at least in the portion facing the anode foil 3.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a wound type solid electrolytic capacitor having a solid electrolyte containing a conductive polymer, and a method for manufacturing the same. [Background technology]

[0002] Electrolytic capacitors using valve metals such as tantalum or aluminum can be small and have large capacitance by enlarging the surface area of ​​the valve metal serving as the anode side electrode by forming it into a sintered body or etched foil, etc. In particular, solid electrolytic capacitors are small, have large capacitance, and have low equivalent series resistance, and are easy to form into chips and suitable for surface mounting, making them indispensable for miniaturizing, improving the functionality, and reducing the cost of electronic devices.

[0003] Known examples of solid electrolytes include manganese dioxide and 7,7,8,8-tetracyanoquinodimethane (TCNQ) complexes. In recent years, conductive polymers derived from monomers with π-conjugated double bonds, such as poly(3,4-ethylenedioxythiophene) (PEDOT), which has excellent adhesion to the dielectric oxide film formed on the surface of the anode foil, have rapidly become popular as solid electrolytes. Polyanions such as organic sulfonic acids are used as dopants in conductive polymers during chemical oxidative polymerization or electrolytic oxidative polymerization, resulting in high conductivity.

[0004] Furthermore, a so-called hybrid type solid electrolytic capacitor has been proposed in which a solid electrolyte layer is formed on a capacitor element in which an anode foil and a cathode foil face each other, and the gaps in the capacitor element are impregnated with an electrolyte (see, for example, Patent Document 1). In a solid electrolytic capacitor that also uses an electrolyte, the electrolyte serves to repair defects in the dielectric oxide film, thereby reducing the leakage current of the solid electrolytic capacitor. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2006-114540 A Summary of the Invention [Problem to be solved by the invention]

[0006] Hereinafter, a solid electrolytic capacitor with only a solid electrolyte layer and a solid electrolytic capacitor using both a solid electrolyte layer and an electrolytic solution are also simply referred to as a solid electrolytic capacitor. A typical structure of a solid electrolytic capacitor is a capacitor element formed by winding an anode foil having a dielectric oxide film formed on the surface of an enlarged aluminum foil and a cathode foil with a separator interposed therebetween, and the capacitor element is provided with a solid electrolyte layer or a solid electrolyte layer and an electrolytic solution as an electrolyte. In the field of such solid electrolytic capacitors, there is always a demand for further reduction in leakage current caused by defects in the dielectric oxide film. However, repair of defects by electrolytic solution cannot be expected in a solid electrolytic capacitor using only a solid electrolyte. In addition, even in a solid electrolytic capacitor using electrolytic solution, repair of defects cannot be expected if the defective parts are not filled with electrolytic solution.

[0007] The present invention has been proposed to solve the above problems, and an object of the present invention is to provide a solid electrolytic capacitor with reduced leakage current and a method for manufacturing the same. [Means for solving the problem]

[0008] The present inventors have found that in the case of a wound solid electrolytic capacitor, the anode-side drawer terminal causes defects in the dielectric oxide film during winding. Compared with damage caused by bending stress applied to the entire anode foil during winding, the defects caused by the drawer terminal may be difficult to completely repair even in the repair process of the dielectric oxide film in the manufacturing process of the solid electrolytic capacitor. In addition, when the solid electrolytic capacitor is placed on a wiring board such as a circuit board, stress is applied to the drawer terminal, and the stress is transmitted to the contact part between the drawer terminal and the anode foil, which may damage the dielectric oxide film on the surface of the anode foil and form a defect. In addition, a dielectric oxide film is also formed on the surface of the drawer terminal on the anode side. The dielectric oxide film on the surface of the drawer terminal may be formed by immersing the drawer terminal in a chemical conversion solution before connecting it to the anode foil, or by chemical conversion of the surface of the drawer terminal when a capacitor element produced by winding an anode foil connected to the drawer terminal is repaired and chemically converted. The dielectric oxide film formed on the lead terminal may also have defects. It has been found that defects in the dielectric oxide film formed on the anode foil and the lead terminal are one of the causes of the increase in leakage current of solid electrolytic capacitors. Furthermore, as a result of intensive research, it has been found that the increase in leakage current occurs when a conductive polymer is present near the defect and there is little or no electrolyte near the defect. In other words, it has been found that if there is no conductive polymer near the defect, the leakage current can be suppressed. Even in solid electrolytic capacitors that also use electrolyte, the conductive polymer is first impregnated into the capacitor element and then the electrolyte is impregnated, so that the conductive polymer clogs the gap between the lead terminal and the electrode foil, making it difficult for the electrolyte to penetrate, and therefore if a conductive polymer is present in the defect caused by the lead terminal, leakage current will occur.

[0009] The present invention was made based on this finding, and is characterized in that it comprises an anode foil having a dielectric oxide coating formed thereon, a lead-out terminal connected to the anode foil, a capacitor element including the anode foil, and a solid electrolyte including a conductive polymer formed within the capacitor element, wherein a coating layer that repels a conductive polymer-forming solution is formed between the anode foil and the lead-out terminal.

[0010] By forming a coating layer that repels the conductive polymer forming solution between the anode foil and the draw-out terminal, the conductive polymer forming solution is prevented from penetrating between the anode foil and the draw-out terminal. This makes it possible to prevent the conductive polymer from adhering to the vicinity of a defect caused by the draw-out terminal between the anode foil and the draw-out terminal, thereby suppressing leakage current. In addition, when a defect exists in the dielectric oxide coating on the surface of the draw-out terminal, it is possible to prevent the conductive polymer from adhering to the vicinity of the defect, which is expected to have the effect of suppressing leakage current. The coating layer may be formed on at least a portion of the lead terminal facing the anode foil.

[0011] The coating layer may be formed at least on the lead-out terminal lead-out end face side of the capacitor element from the connection portion of the lead-out terminal with the anode foil.

[0012] The coating layer may have a thickness of 10 nm or more.

[0013] The contact angle between the surface of the coating layer and the conductive polymer forming solution may be 80° or more.

[0014] The coating layer may have a thickness of 10 nm or more and 80 nm or less.

[0015] The coating layer may be incompatible with a solution in which the capacitor element is immersed in a repair chemical conversion process.

[0016] This method of manufacturing a solid electrolytic capacitor includes a winding step of connecting a lead terminal to a cathode foil and an anode foil having a dielectric oxide coating formed thereon, and then winding the cathode foil and the anode foil while rolling up the lead terminal to form a capacitor element, and an electrolyte formation step of, after the winding step, immersing a surface of the capacitor element opposite to an end surface of the capacitor element from which the lead terminal connected to the anode-side foil leads out in a solution that forms a solid electrolyte, and is characterized in that a coating layer that repels a conductive polymer-forming solution is formed on at least the anode-side lead terminal.

[0017] When the capacitor element is immersed in the conductive polymer forming solution, a coating layer that repels the dispersion liquid is formed near the voids, preventing the solution from penetrating into the voids and preventing the solution from reaching defects in the dielectric oxide film formed on the surface of the anode foil caused by the draw-out terminal. Therefore, no conductive polymer is present near the defects in the voids, and leakage current is suppressed. In addition, if there are defects in the dielectric oxide film on the surface of the draw-out terminal, adhesion of the conductive polymer to the defects can be suppressed, and the effect of suppressing leakage current can also be expected. Effect of the Invention

[0018] According to the present invention, the probability that a conductive polymer is present near a defective portion caused by a lead-out terminal is reduced, so that leakage current can be suppressed. [Brief description of the drawings]

[0019] [Figure 1] 2A and 2B are diagrams illustrating an example of a capacitor element before being housed in a case according to the present embodiment. [Diagram 2] 2 is a cross-sectional view taken along a virtual line connecting an anode-side lead terminal and a cathode-side lead terminal of a capacitor element according to the embodiment. FIG. [Diagram 3] 3(a) is a diagram showing a cross section taken along imaginary line aa in FIG. 2, and FIG. 3(b) is a diagram showing a cross section taken along imaginary line bb in FIG. [Figure 4] 4 is an enlarged view of a connection portion between an anode foil and an anode-side extraction terminal according to the embodiment. FIG. [Diagram 5] FIG. 2 is a diagram showing a capacitor element according to the embodiment in an expanded state. [Figure 6] 5A and 5B are diagrams showing connections between lead-out terminals and electrode foils according to the embodiment; [Figure 7] FIG. 2 is a schematic diagram showing a state in which a conductive polymer dispersion liquid is impregnated into a capacitor element. [Figure 8] FIG. 2 is a diagram showing the position where a coating layer is formed in Example 1. [Figure 9] FIG. 13 is a diagram showing the position where a coating layer is formed in Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Hereinafter, a solid electrolytic capacitor according to an embodiment of the present invention will be described. In this embodiment, a solid electrolytic capacitor that also uses an electrolytic solution will be described as an example. Note that the present invention is not limited to the embodiment described below. (First embodiment) A solid electrolytic capacitor according to a first embodiment will be described with reference to Figs. 1 to 5. Fig. 1 is a diagram showing an example of a capacitor element before being housed in a case according to the first embodiment. The solid electrolytic capacitor 1 according to the first embodiment is a passive element that stores and discharges electric charge by electrostatic capacitance. The solid electrolytic capacitor 1 has, for example, a wound type capacitor element 2. The capacitor element 2 has an anode foil 3 having a dielectric oxide film formed on its surface and a cathode foil 4 opposed to each other via a separator 5, and a solid electrolyte is formed. The solid electrolyte is in close contact with the dielectric oxide film formed on the anode foil 3 and functions as a true cathode. The solid electrolytic capacitor 1 may be filled with an electrolytic solution in addition to the solid electrolyte.

[0021] The anode foil 3 is a long foil made of a valve metal. Examples of the valve metal include aluminum, tantalum, niobium, niobium oxide, titanium, hafnium, zirconium, zinc, tungsten, bismuth, and antimony. The purity is preferably about 99.9% or more, but impurities such as silicon, iron, copper, magnesium, and zinc may be included. The anode foil 3 is formed by forming a surface expansion layer on a stretched foil and forming a dielectric oxide coating on the surface of the surface expansion layer. The surface expansion layer is formed by spongy pits and tunnel-like pits dug in the thickness direction from the foil surface. Alternatively, the surface expansion layer may be formed by sintering valve metal powder, or by evaporating a coating of metal particles or the like onto the foil.

[0022] A dielectric oxide film layer is formed on the surface of the surface-expanding layer. For example, if the anode foil 3 is made of aluminum, the dielectric oxide film layer is an aluminum oxide layer formed by oxidizing the porous structure region. This dielectric oxide film is formed by chemical conversion treatment in which a voltage is applied in a solution that does not contain halogen ions, such as an acid such as ammonium borate, ammonium phosphate, or ammonium adipate, or an aqueous solution of such an acid.

[0023] The cathode foil 4 is a metal foil such as aluminum foil, similar to the anode foil 3, and the surface of which is only subjected to an etching process.

[0024] An anode side lead terminal 6-1 and a cathode side lead terminal 6-2 for connecting the respective electrodes to the outside are connected to the anode foil 3 and the cathode foil 4 by stitching, ultrasonic welding, or the like. The solid electrolytic capacitor 1 is mounted to an electric circuit or an electronic circuit via the lead terminals 6-1 and 6-2. The lead terminals 6-1 and 6-2 are, for example, composed of an aluminum wire and a metal wire 9. The aluminum wire is composed of a flat plate portion 7 formed by crushing one end of a round bar shape by pressing or the like, and an unpressed round bar portion 8 on the other end. The tip of the round bar portion 8 and the metal wire 9 are connected by arc welding or the like. The anode side lead terminal 6-1 may have a dielectric oxide coating formed on the surface of the flat plate portion 7 by chemical conversion treatment.

[0025] The flat portion 7 of the lead-out terminal 6-1 is brought into contact with one side of the anode foil 3, and the round bar portion 8 and the metal wire 9 are allowed to protrude from the anode foil 3 so as to be perpendicular to the long side of the anode foil 3, thereby connecting the lead-out terminal 6-1 to the anode foil 3. The lead-out terminal 6-2 and the cathode foil 4 are also connected in the same manner as the anode side. The connection can be made by one of various connection means such as stitch connection, cold pressure welding, ultrasonic welding, or laser welding.

[0026] The anode foil 3 connected to the lead terminal 6-1 and the cathode foil 4 connected to the lead terminal 6-2 are overlapped and wound with a separator 5 interposed therebetween. Examples of the separator 5 include cellulose papers such as kraft, Manila hemp, esparto, hemp, and rayon, and mixtures thereof, polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and derivatives thereof, polytetrafluoroethylene-based resins, polyvinylidene fluoride-based resins, vinylon-based resins, polyamide-based resins such as aliphatic polyamides, semi-aromatic polyamides, and fully aromatic polyamides, polyimide-based resins, polyethylene resins, polypropylene resins, trimethylpentene resins, polyphenylene sulfide resins, acrylic resins, and polyvinyl alcohol resins, and these resins can be used alone or in combination.

[0027] FIG. 2 is a cross-sectional view taken along a virtual line connecting the anode-side lead terminal 6-1 and the cathode-side lead terminal 6-2 of the capacitor element 1. FIG. 3(a) is a cross-sectional view taken along the virtual line a-a in FIG. 2, and FIG. 3(b) is a cross-sectional view taken along the virtual line b-b in FIG. 2. FIG. 4 is an enlarged view of the connection between the anode foil 3 and the lead terminal 6-1 in FIG. 2. In FIG. 4, the right side of the drawing shows the inner circumferential side (center side) X of the capacitor element 2, and the left side of the drawing shows the outer circumferential side Y of the capacitor element 2. FIG. 5 is a view showing the capacitor element 2 in FIG. 1 in an expanded state. In FIG. 5, the lower side of the drawing shows the inner circumferential side (center side) X of the capacitor element 2, and the upper side of the drawing shows the outer circumferential side Y of the capacitor element 2. The lead terminal 6-1 of the anode foil 3 is connected to the surface of the inner circumferential side X of the capacitor element 2, and the lead terminal 6-2 of the cathode foil 4 is connected to the surface of the outer circumferential side Y of the capacitor element 2.

[0028] As shown in Figs. 1 to 3, the capacitor element 2 has a wound body shape. The center of the capacitor element 2 is a hole 10 penetrating from one end face to the other end face of the capacitor element 2 because the winding shaft used during winding is removed after winding. The lead terminals 6-1, 6-2 are wound by the winding process and lead out from lead terminal lead end faces 11 of the lead terminals 6-1, 6-2, which are one end faces of the capacitor element 2. The lead terminals 6-1, 6-2 are sandwiched between the winding layer to which the lead terminals are connected and the winding layer one periphery inside it. By sandwiching the lead terminals 6-1, 6-2, crescent-shaped holes 12 are generated in the width direction of the lead terminals 6-1, 6-2, in other words, around both ends in the circumferential direction of the capacitor element 2. Crescent-shaped hole 12 extends through capacitor element 2 along the axis of capacitor element 2, and has openings at both end surfaces, that is, lead-out terminal leading end surface 11 of capacitor element 2 and the end surface opposite thereto.

[0029] Gaps 13-1 and 13-2 are generated between the anode foil 3 and the lead terminal 6-1. These gaps 13-1 and 13-2 are due to the connection method between the anode foil 3 and the lead terminal 6-1 and the structure of the capacitor element 2. One of the reasons due to the structure of the capacitor element 2 is that the lead terminal 6-1 on the anode side is disposed closer to the center of the capacitor element 2 than the anode foil 3. As shown in FIG. 4, the end 3-1 in the length direction of the part of the anode foil 3 facing the lead terminal 6-1, in other words, in the direction perpendicular to the circumferential direction of the capacitor element 2, is slightly along the outer periphery side Y. Since the dielectric oxide film formed on the surface of the anode foil 3 is hard and brittle, the anode foil 3 is harder than the cathode foil 4, and even when rolled, the restoring force acts on the outer periphery of the capacitor element 2. Therefore, the connection part with the anode foil 3 maintains contact with the draw-out terminal 6-1, but the vicinity of the end 3-1 away from the connection part with the draw-out terminal 6-1 is slightly warped toward the outer periphery side Y, and gaps 13-1 and 13-2 are generated between the anode foil 3 and the draw-out terminal 6-1. This phenomenon is prominent when the anode side draw-out terminal 6-1 is connected to the center side X of the capacitor element 2 with respect to the anode foil 3, but is not limited to this. When the anode side draw-out terminal 6-1 is connected to the outer periphery side Y of the capacitor element 2 with respect to the anode foil 3, the anode foil 3 is curved around the connection part with the draw-out terminal 6-1 because the capacitor element 2 has a wound structure, and the end in the width direction of the draw-out terminal 6-1, in other words, in the circumferential direction of the capacitor element 2, is separated from the anode foil 3, and gaps 13-1 and 13-2 may be generated, so that a similar problem is considered to occur.

[0030] One of the stresses caused by the method of connecting the anode foil 3 and the lead terminal 6-1 is the stress applied to the anode foil 3 during connection. For example, the connection is achieved by inserting a stitch needle into the flat portion 7 of the lead terminal 6-1 overlapping the anode foil 3, penetrating the cut-and-raised piece 23 generated on the lead terminal 6-1 into the anode foil 3, and then pressurizing the cut-and-raised piece 23 to sandwich the anode foil 3 between the flat portion 7 and the cut-and-raised piece 23. In this way, the lead terminal 6-1 and the anode foil 3 are connected.

[0031] As shown in FIG. 6A, the connection is made by placing anode foil 3 on lower die 19, arranging flat portion 7 of lead terminal 6-1 in a position to close through hole 20 of lower die 19, and sandwiching it with upper die 21. 6B, stitch needle 22 is lowered from the lead-out terminal 6-1 side. When stitch needle 22 penetrates anode foil 3 from the lead-out terminal 6-1 side, cut-and-raised piece 23 generated in lead-out terminal 6-1 penetrates anode foil 3 together with stitch needle 22. Next, as shown in FIG. 6C(1), the stitch needle 22 is raised, and then the forming die 24 waiting in the through hole 20 of the lower die 19 is raised. As the forming die 24 rises, the cut-and-raised piece 23 is pressed and shaped between the forming die 24 and the upper die 21, and the cut-and-raised piece 23 is connected to the back side of the anode foil 3. As a result, the anode foil 3 is sandwiched between the lead terminal 6-1 and the cut-and-raised piece 23, and is electrically connected to the lead terminal 6-1. In this stitching connection, as shown in FIG. 6C(2) (broken line part a in FIG. 6C(1)), when the cut-and-raised piece 23 is pressed, the stress P1 applied from the forming die 24 is transmitted as stress P2 through the cut-and-raised piece 23 to the periphery of the connection part of the anode foil 3 with the lead terminal 6-1. A hard and brittle dielectric oxide coating is formed on the surface of the anode foil 3, so that the anode foil 3 has low flexibility. Therefore, when the stress P2 is applied, a reaction force, that is, a stress P3 in a direction away from the lead terminal 6-1, is generated in a portion away from the connection portion. In this state, when lower die 19 and upper die 21 are separated from anode foil 3, gaps 13-1, 13-2 are created between anode foil 3 and the widthwise ends of lead-out terminal 6-1, in other words, the circumferential ends of capacitor element 2, as shown in Figure 6D.

[0032] Although the stitching method has been mentioned as a method for connecting the anode foil 3 and the lead terminal 6-1, the method is not limited to this and can also be performed using cold pressure welding or ultrasonic welding. In the cold pressure welding method, the anode foil 3 is placed on the flat portion 7 of the lead terminal 6-1, and the laminated portion with the flat portion 7 is pressed from the anode foil 3 side with a cold pressure welding die to connect the lead terminal 6-1 and the flat portion 7. In ultrasonic welding, anode foil 3 is placed on flat portion 7 of lead-out terminal 6-1, and pressure and ultrasonic vibration are applied to the laminated portion with flat portion 7 from the anode foil 3 side to connect lead-out terminal 6-1 and flat portion 7. Both the cold pressure welding method and the ultrasonic welding method include a process of pressing the draw-out terminal 6-1 from the side of the anode foil 3. Therefore, as with the stitching method, in the pressed part, the anode foil 3 is pressed toward the draw-out terminal 6-1 side, and the draw-out terminal 6-1 and the anode foil 3 are in close contact, but in the part away from the pressed part, a stress acts in the direction that moves the anode foil 3 away from the draw-out terminal 6-1 due to the reaction of the pressing. Therefore, even when cold pressure welding and ultrasonic welding are used, gaps 13-1 and 13-2 may occur between anode foil 3 and the widthwise ends of lead terminal 6-1, in other words, between the circumferential ends of capacitor element 2.

[0033] A coating layer 14 is formed between the anode foil 3 and the draw-out terminal 6-1. The coating layer 14 is formed by a coating agent made of, for example, a silicone-based resin or a fluorine-based resin. The coating layer 14 may be formed between the anode foil 3 and the draw-out terminal 6-1. In the first embodiment, the coating layer 14 is formed by applying a coating agent to a portion of the draw-out terminal 6-1 that contacts the anode foil 3. When forming the coating layer 14 on the draw-out terminal 6-1, the coating layer 14 may be formed on at least a portion of the flat plate portion 7 that contacts the anode foil 3 of the draw-out terminal 6-1, from a connection portion 15-1 with the anode foil 3 close to the metal wire 9 to a portion facing the draw-out terminal lead-out end surface 11. The coating layer 14 may be formed on a portion of the flat plate portion 7 of the draw-out terminal 6-1 that contacts the anode foil 3, or may be formed on the entire draw-out terminal 6-1. It is sufficient for the coating layer 14 to be able to repel the solvent of the conductive polymer forming solution so that the conductive polymer forming solution does not enter the aforementioned gap portion 13-1.

[0034] When the thickness of the coating layer 14 is 1.5 nm or more, leakage current tends to be small. The thickness of the coating layer 14 is preferably 10 nm or more. Furthermore, in consideration of the connectivity with the extraction terminal 6-1, the thickness is preferably 80 nm or less. Therefore, the thickness is more preferably 10 nm or more and 80 nm or less. The thickness of the coating layer 14 can be adjusted appropriately by adjusting the concentration of the base material relative to the solvent. For example, in this embodiment, it is preferable to set the concentration to 0.1 wt % to 2.0 wt %.

[0035] It is also preferable that the contact angle between the surface of the coating layer 14 and the conductive polymer forming solution is equal to or greater than 80°, which tends to reduce leakage current.

[0036] Furthermore, when the anode foil 3 and the lead terminal 6-1 are connected by the stitch connection method, it is preferable that the coating layer 14 does not crack or peel off due to the stress applied to the lead terminal 6-1 when a stitch needle is pierced to form the cut-and-raised piece 23. On the other hand, when the cut-and-raised piece 23 is pressed and shaped by the forming die 24 and connected to the back side of the anode foil 3, it is only necessary that the coating layer 14 at the portion of the cut-and-raised piece 23 that comes into contact with the anode foil 3 has a strength sufficient to cause a crack. For example, when the cut-and-raised piece 23 is formed by piercing a stitch needle, a load of about 10 MPa is applied to the surface of the lead terminal 6-1. Therefore, it is preferable that at least the coating layer 14 has a strength that does not crack or peel off even when a load of 10 MPa is applied. In addition, since the coating layer 14 does not crack or peel off, contact between the conductive polymer and the anode foil 3 or the bare metal of the lead terminal 6-1 is suppressed, and leakage current is reduced. On the other hand, when the cut-and-raised piece 23 is pressed and formed by the forming die 24 and connected to the back side of the anode foil 3, a stress of about 50 MPa is applied to the cut-and-raised piece 23. At this time, the cut-and-raised piece 23 stretches due to the stress, and the surface of the cut-and-raised piece 23 also stretches to follow, and the coating layer 14 becomes thin, or the coating layer 14 formed on the surface cracks, exposing the bare metal part of the cut-and-raised piece 23. Since the coating layer 14 has insulating properties, electrical connectivity is improved by contacting the anode foil 3 with the thin portions of the coating layer 14 or with the exposed portions of the base metal.

[0037] After the anode foil 3, the cathode foil 4, and the separator 5 are wound, a solid electrolyte is formed in the capacitor element 2. The solid electrolyte includes a conductive polymer. The conductive polymer is a doped conjugated polymer. The conjugated polymer is obtained by chemical oxidative polymerization or electrolytic oxidative polymerization of a monomer having a π-conjugated double bond or a derivative thereof.

[0038] This solid electrolyte is interposed between anode foil 3 and cathode foil 4 and is in close contact with the dielectric oxide film. However, as described below, by preventing adhesion of the conductive polymer forming solution by coating layer 14, the amount of solid electrolyte in the periphery of coating layer 14 is smaller than in other parts of capacitor element 2.

[0039] The capacitor element 2 with the solid electrolyte formed therein is housed in a cylindrical exterior case 16 with a bottom made of aluminum or the like (not shown), and the opening is sealed by crimping with a sealing member 17 made of an elastic body or a composite material of an elastic body and a hard body, thereby forming the solid electrolytic capacitor 1. Second Embodiment In the first embodiment, the coating layer 14 is formed on the lead-out terminal 6-1, but in the second embodiment, the coating layer 14 is formed on the surface of the anode foil 3 to which the lead-out terminal 6-1 is connected. The other configurations are similar to those of the first embodiment, and therefore the description thereof will be omitted.

[0040] (Manufacturing method) An example of a method for manufacturing this solid electrolytic capacitor 1 is shown below. First, a coating layer forming step is performed to form a coating layer 14 on the draw-out terminal 6-1. Next, a winding step is performed to wind the anode foil 3 connected to the draw-out terminal 6-1 on which the coating layer 14 is formed and the cathode foil 4 connected to the draw-out terminal 6-2 with a separator 5 interposed between them to produce a capacitor element 2. Next, a repair chemical formation step is performed to immerse the capacitor element 2 in a chemical formation solution to repair the dielectric oxide film. Note that the repair chemical formation step includes a step of removing the chemical formation solution from the capacitor element 2 after the repair chemical formation using a chemical formation solution cleaning solution such as pure water.

[0041] Next, after a drying process for removing the chemical conversion solution and the chemical conversion solution cleaning solution, an electrolyte formation process is performed in which the capacitor element 2 is impregnated with a dispersion liquid of a conductive polymer to form a solid electrolyte. When an electrolyte solution is used in combination, an electrolyte impregnation process is performed in which the capacitor element 2 is further impregnated with the electrolyte solution.

[0042] In the coating layer forming step, a coating layer 14 that repels a conductive polymer forming solution described later is formed between the anode foil 3 and the draw-out terminal 6-1. The coating layer 14 may be formed anywhere between the anode foil 3 and the draw-out terminal 6-1, and may be formed on the surface of the draw-out terminal 6-1 or on the surface of the anode foil 3. When the coating layer 14 is formed on the draw-out terminal 6-1, it may be formed on the surface of the flat plate portion 7 between the round bar portion 8 and the connection portion 15-1 close to the metal wire 3 of the connection portion 15 with the anode foil 3 of the draw-out terminal 6-1, among the portions of the draw-out terminal 6-1 that contact the anode foil 3, and may be formed on the entire surface of the flat plate portion 7 facing the anode foil 3 of the draw-out terminal 6-1 or on the entire surface of the draw-out terminal 6-1. The coating layer 14 may be formed by applying or spraying a coating agent on the portion where the coating layer 14 is to be formed, or when the coating layer 14 is to be formed on the entire surface of the draw-out terminal 6-1, the draw-out terminal 6-1 may be immersed in the coating agent. When the coating layer 14 is formed on the surface of the anode foil 3, it may be formed in the portion of the anode foil 3 that contacts the lead-out terminal 6-1, between the connection portion 15-1 between the lead-out terminal 6-1 and the anode foil 3 and the end of the lead-out terminal lead-out end face 11, or may be formed on the surface that contacts the lead-out terminal 6-1. The coating agent only needs to repel the conductive polymer forming solution, and more specifically, it needs to repel the solvent of the solution. For example, fluorine-based resins such as polytetrafluoroethylene (PTFE), perfluoroalkoxyalkane (PFA), perfluoroethylenepropene copolymer (FEP), ethylenetetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVDF), and silicone-based resins such as linear dimethylpolysiloxane (terminal trimethylsilyl group), linear dimethylpolysiloxane (terminal OH group), cyclic dimethylpolysiloxane, linear dialkylpolysiloxane, reticular methylpolysiloxane, reticular methyl-phenyl-polysiloxane, reticular methyl-methoxy-polysiloxane, and methyl-hydrogen-polysiloxane can be used alone or in combination. Examples of mixtures include perfluoropolyether-modified silanes having perfluoropolyether groups and alkoxysilyl groups in the molecule. The coating layer forming step may include a step of removing the coating layer 14 from a portion intended for connection with the lead-out terminal 6-1 after forming the coating layer 14. For example, the portion of the coating layer 14 intended for connection with the lead-out terminal 6-1 may be peeled off by laser irradiation.

[0043] In the winding process, defects such as voids, cracks, or scratches occur in various places in the dielectric oxide film due to insufficient formation of the dielectric oxide film or bending stress caused by winding. Therefore, in the repair chemical treatment, the capacitor element 2 is immersed in a chemical conversion liquid. The chemical conversion liquid for the repair chemical conversion is an aqueous solution in which a phosphoric acid-based solution such as ammonium dihydrogen phosphate or diammonium hydrogen phosphate, a boric acid-based solution such as ammonium borate, or an adipic acid-based solution such as ammonium adipate is dissolved in water. The immersion time is preferably 5 minutes or more and 120 minutes or less. Thereafter, in order to remove the chemical conversion liquid from the capacitor element 2, the capacitor element 2 immersed in the chemical conversion liquid is washed with a chemical conversion liquid washing liquid such as pure water.

[0044] Furthermore, in the winding process, physical contact occurs between the lead terminal 6-1 and the dielectric oxide film. This contact causes large defects such as cracks and scratches in the area of ​​the anode foil 3 that comes into contact with the lead terminal 6-1. In particular, defects are most likely to occur in the area that comes into contact with the corner of the flat portion 7 of the lead terminal 6-1.

[0045] The defects caused by the presence of the lead terminals 6-1 are difficult to completely repair in the repair anodizing process, and therefore the defects caused by the presence of the lead terminals 6-1 remain even after the repair anodizing process.

[0046] After the repair chemical conversion step, the chemical conversion solution and the chemical conversion solution cleaning solution are removed by drying. In this drying step, the capacitor element 2 is exposed to a high heat environment of 100° C. or higher for 30 minutes or longer. In addition to drying by heat, the solvent may be volatilized by vacuum drying.

[0047] After drying the capacitor element 2, a solid electrolyte is formed. In the electrolyte formation process, a dispersion liquid in which a conductive polymer is dispersed is first prepared. This dispersion liquid is an example of a solution for forming a conductive polymer. The conductive polymer is a doped conjugated polymer. As the conjugated polymer, any known one can be used without any particular limitation. For example, polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene, polyphenylene, polyphenylenevinylene, polyacene, polythiophenevinylene, etc. can be mentioned. These conjugated polymers may be used alone, or two or more kinds may be combined, or they may be copolymers of two or more kinds of monomers.

[0048] Among the above-mentioned conjugated polymers, a conjugated polymer obtained by polymerizing thiophene or a derivative thereof is preferred, and a conjugated polymer obtained by polymerizing 3,4-ethylenedioxythiophene (i.e., 2,3-dihydrothieno[3,4-b][1,4]dioxine), 3-alkylthiophene, 3-alkoxythiophene, 3-alkyl-4-alkoxythiophene, 3,4-alkylthiophene, 3,4-alkoxythiophene, or a derivative thereof is preferred.

[0049] The thiophene derivative is preferably a compound selected from thiophenes having substituents at the 3rd and 4th positions, and the substituents at the 3rd and 4th positions of the thiophene ring may form a ring together with the carbons at the 3rd and 4th positions. The number of carbon atoms of the alkyl group or alkoxy group is preferably 1 to 16, and in particular, a polymer of 3,4-ethylenedioxythiophene called EDOT, that is, poly(3,4-ethylenedioxythiophene) called PEDOT, is particularly preferred. In addition, alkylated ethylenedioxythiophene in which an alkyl group is added to 3,4-ethylenedioxythiophene may be used, and examples thereof include methylated ethylenedioxythiophene (i.e., 2-methyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine) and ethylated ethylenedioxythiophene (i.e., 2-ethyl-2,3-dihydro-thieno[3,4-b][1,4]dioxine).

[0050] The dopant may be any known dopant without any particular limitation. For example, inorganic acids such as boric acid, nitric acid, and phosphoric acid, and organic acids such as acetic acid, oxalic acid, citric acid, ascot acid, tartaric acid, squaric acid, rhodizonic acid, croconic acid, salicylic acid, p-toluenesulfonic acid, 1,2-dihydroxy-3,5-benzenedisulfonic acid, methanesulfonic acid, trifluoromethanesulfonic acid, borodisalicylic acid, bisoxalate borate acid, sulfonylimide acid, dodecylbenzenesulfonic acid, propylnaphthalenesulfonic acid, and butylnaphthalenesulfonic acid can be mentioned. In addition, examples of polyanions include polyvinylsulfonic acid, polystyrenesulfonic acid, polyallylsulfonic acid, polyacrylicsulfonic acid, polymethacrylic acid, poly(2-acrylamido-2-methylpropanesulfonic acid), polyisoprene sulfonic acid, polyacrylic acid, polymethacrylic acid, and polymaleic acid.

[0051] These dopants may be used alone or in combination of two or more. Furthermore, these dopants may be polymers of a single monomer or copolymers of two or more monomers. Furthermore, the dopants may be polymers or monomers.

[0052] For example, the conductive polymer is preferably a mixture of PEDOT powder and a solid content of a dopant made of polystyrene sulfonic acid. In order to improve the impregnation and electrical conductivity of the conductive polymer dispersion, various additives may be added to the conductive polymer or neutralization may be performed by adding cations.

[0053] The solvent for the dispersion may be any solvent that disperses the conductive polymer particles or powder, and may be, for example, water, an organic solvent, or a mixture thereof. Suitable examples of the organic solvent include polar solvents, alcohols, esters, hydrocarbons, carbonate compounds, ether compounds, chain ethers, heterocyclic compounds, and nitrile compounds.

[0054] Examples of polar solvents include N-methyl-2-pyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide. Examples of alcohols include methanol, ethanol, propanol, and butanol. Examples of esters include ethyl acetate, propyl acetate, and butyl acetate. Examples of hydrocarbons include hexane, heptane, benzene, toluene, and xylene. Examples of carbonate compounds include ethylene carbonate and propylene carbonate. Examples of ether compounds include dioxane and diethyl ether. Examples of chain ethers include ethylene glycol dialkyl ether, propylene glycol dialkyl ether, polyethylene glycol dialkyl ether, and polypropylene glycol dialkyl ether. Examples of heterocyclic compounds include 3-methyl-2-oxazolidinone. Examples of nitrile compounds include acetonitrile, glutarodinitrile, methoxyacetonitrile, propionitrile, and benzonitrile.

[0055] Incidentally, ethylene glycol is suitable as a solvent for the dispersion liquid. Ethylene glycol is one of the solvents for the electrolyte solution described below, and even if it remains in the capacitor element 2, it does not become an impurity, and furthermore, among the electrical properties of the product, it can reduce the ESR in particular.

[0056] 7 is a schematic diagram showing how a wound body is impregnated with a dispersion liquid 18 of a conductive polymer. As shown in FIG. 7, after the dispersion liquid 18 is prepared, the end face of the capacitor element 2 opposite to the lead-out terminal derivation end face 11 is immersed in the dispersion liquid 18. The dispersion liquid 18 creeps up from the opening of the hole 10 opposite to the lead-out terminal derivation end face 11 of the capacitor element 2 to the opening on the lead-out terminal derivation end face 11 side. The dispersion liquid 18 that creeps up to the lead-out terminal derivation end face 11 of the capacitor element 2 and the dispersion liquid 18 that is immersed in the end face opposite to the lead-out terminal derivation end face 11 permeate toward the center of the capacitor element 2, and the conductive polymer is distributed throughout. At this time, gaps 13-1 and 13-2 are generated between the flat portion 7 of the lead terminal 6-1 on the lead terminal lead end surface 11 side of the capacitor element 2 and the anode foil 3 due to the restoring force of the anode foil 3 and the stress when the anode foil 3 and the lead terminal 6-1 are connected. The gap 13-2 on the end face side opposite to the lead terminal lead end surface 11 of the capacitor element 2 is closed at the top, so that the dispersion liquid 18 is difficult to enter. On the other hand, the gap 13-1 on the lead terminal lead end surface 11 side is structured so that the dispersion liquid 18 can easily enter because the top of the gap 13-1 is open. However, as in this embodiment, the coating layer 14 is formed at least near the intrusion portion, so that the dispersion liquid 18 is difficult to enter. Therefore, the conductive polymer is difficult to adhere to the vicinity of the defect portion generated by the presence of the lead terminal 6-1. On the other hand, the conductive polymer spreads throughout the capacitor element 2 except around the gaps 13-1 and 13-2.

[0057] The impregnation time can be set appropriately depending on the size of the capacitor element 2. Long-term impregnation does not adversely affect the characteristics. When impregnating the capacitor element 2, decompression treatment or pressurization treatment may be performed as necessary to promote impregnation. The impregnation process may be repeated multiple times. The solvent of the conductive polymer dispersion liquid is evaporated and removed by drying as necessary. Heat drying or reduced-pressure drying may be performed as necessary.

[0058] In this electrolyte formation step, a conductive polymer dispersion solution is used to form the solid electrolyte, but a conductive polymer solution in which a conductive polymer is dissolved, such as a soluble conductive polymer solution, may be used to form the solid electrolyte. The difference is that the former is a dispersion, so the conductive polymer is dispersed in the solution without dissolving, whereas the latter soluble conductive polymer solution is in a state where the conductive polymer is dissolved in the solution. The solid electrolyte may be formed in the capacitor element 2 by any of the processes, and the present invention is not limited to these methods.

[0059] The solid electrolyte may be formed by using a conductive polymer dispersion solution or a soluble conductive polymer solution as described above, but is not limited thereto. For example, the capacitor element 2 may be immersed in a solution containing a precursor of the conductive polymer, and then a solid electrolyte by chemical polymerization or a solid electrolyte by electrolytic polymerization may be formed. The conductive polymer layer by chemical polymerization is formed by immersing the capacitor element in a mixed solution of 3,4-ethylenedioxythiophene as a polymerizable monomer and an alcohol solution (such as ethanol) of ferric paratoluenesulfonate as an oxidizing agent, and heating the capacitor element to cause a polymerization reaction of the conductive polymer. Also, before or after this heating process, a water washing process may be performed to remove unreacted monomers and excess monomers by washing with water. The solid electrolyte by electrolytic polymerization is formed by forming a solid electrolyte on the surface of a self-doped conductive polymer layer by electrolytic polymerization. The self-doped conductive polymer layer is used as an electrode and power is supplied from a supply electrode to form a solid electrolyte. A monomer that becomes conductive by electrolytic polymerization can be used as the electrolytic polymerization solution. As the monomer, a thiophene monomer or a pyrrole monomer is preferable. When using these monomers, the capacitor element is immersed in an aqueous solution for electrolytic polymerization containing the monomer and the supporting electrolyte sodium 1-naphthalenesulfonate in a stainless steel container, and a predetermined voltage is applied to it, which allows a solid electrolyte to be uniformly formed from the water-soluble monomer (e.g., thiophene, pyrrole, etc.) by electrolytic polymerization.

[0060] When an electrolytic solution is used as the electrolyte, after the solid electrolyte is formed, the electrolytic solution is impregnated into the capacitor element 2. The electrolytic solution is filled into the voids of the capacitor element 2 in which the solid electrolyte is formed. The electrolytic solution may be impregnated to the extent that the solid electrolyte swells. In the electrolytic solution impregnation step, a depressurization treatment or a pressurization treatment may be performed as necessary.

[0061] The solvent of the electrolyte solution may be a protic organic polar solvent or an aprotic organic polar solvent, either alone or in combination of two or more. The solute of the electrolyte solution may be an anion component or a cation component. The solute is typically a salt of an organic acid, a salt of an inorganic acid, or a salt of a complex compound of an organic acid and an inorganic acid, either alone or in combination of two or more. An acid that becomes an anion and a base that becomes a cation may be added separately to the solvent.

[0062] Examples of the protic organic polar solvent that is the solvent include monohydric alcohols, polyhydric alcohols, and oxyalcohol compounds. Examples of the monohydric alcohols include ethanol, propanol, butanol, pentanol, hexanol, cyclobutanol, cyclopentanol, cyclohexanol, and benzyl alcohol. Examples of the polyhydric alcohols and oxyalcohol compounds include ethylene glycol, propylene glycol, glycerin, methyl cellosolve, ethyl cellosolve, methoxypropylene glycol, dimethoxypropanol, and alkylene oxide adducts of polyhydric alcohols such as polyethylene glycol and polyoxyethylene glycerin. Among these, ethylene glycol is preferred as the solvent. Ethylene glycol causes a change in the higher-order structure of the conductive polymer, resulting in good initial ESR characteristics and good high-temperature characteristics. It is even better if the ethylene glycol is 50 wt% or more in the liquid.

[0063] Representative examples of aprotic organic polar solvents that serve as solvents include sulfones, amides, lactones, cyclic amides, nitriles, and oxides. Examples of sulfones include dimethyl sulfone, ethyl methyl sulfone, diethyl sulfone, sulfolane, 3-methyl sulfolane, and 2,4-dimethyl sulfolane. Examples of amides include N-methylformamide, N,N-dimethylformamide, N-ethylformamide, N,N-diethylformamide, N-methylacetamide, N,N-dimethylacetamide, N-ethylacetamide, N,N-diethylacetamide, and hexamethylphosphoric amide. Examples of lactones and cyclic amides include γ-butyrolactone, γ-valerolactone, δ-valerolactone, N-methyl-2-pyrrolidone, ethylene carbonate, propylene carbonate, butylene carbonate, and isobutylene carbonate. Examples of the nitriles include acetonitrile, 3-methoxypropionitrile, glutaronitrile, etc. Examples of the oxides include dimethyl sulfoxide, etc.

[0064] Examples of organic acids that serve as anion components as solutes include carboxylic acids such as oxalic acid, succinic acid, glutaric acid, pimelic acid, suberic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, maleic acid, adipic acid, benzoic acid, toluic acid, enanthic acid, malonic acid, 1,6-decanedicarboxylic acid, 1,7-octanedicarboxylic acid, azelaic acid, resorcylic acid, phloroglucic acid, gallic acid, gentisic acid, protocatechuic acid, pyrocatechuic acid, trimellitic acid, and pyromellitic acid, as well as phenols and sulfonic acids. Examples of inorganic acids include boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, carbonic acid, and silicic acid. Examples of composite compounds of organic acids and inorganic acids include borodisalicylic acid, borodioxalic acid, borodiglycolic acid, borodimalonic acid, borodisuccinic acid, borodiadipic acid, borodiazelaic acid, borodibenzoic acid, borodimaleic acid, borodilactic acid, borodimalic acid, boroditartaric acid, borodicitric acid, borodiphthalic acid, borodi(2-hydroxy)isobutyric acid, borodiresorcylic acid, borodimethylsalicylic acid, borodinaphthoic acid, borodimandelic acid, and borodi(3-hydroxy)propionic acid.

[0065] In addition, examples of at least one salt of an organic acid, an inorganic acid, and a complex compound of an organic acid and an inorganic acid include ammonium salt, quaternary ammonium salt, quaternary amidinium salt, amine salt, sodium salt, potassium salt, etc. Examples of quaternary ammonium ions of quaternary ammonium salts include tetramethylammonium, triethylmethylammonium, tetraethylammonium, etc. Examples of quaternary amidinium salts include ethyldimethylimidazolinium, tetramethylimidazolinium, etc. Examples of amine salts include salts of primary amines, secondary amines, and tertiary amines. Examples of primary amines include methylamine, ethylamine, propylamine, etc., examples of secondary amines include dimethylamine, diethylamine, ethylmethylamine, dibutylamine, etc., and examples of tertiary amines include trimethylamine, triethylamine, tributylamine, ethyldimethylamine, ethyldiisopropylamine, etc.

[0066] Furthermore, other additives can be added to the electrolytic solution. Examples of additives include alkylene oxide adducts of polyhydric alcohols such as polyethylene glycol and polyoxyethylene glycerin, complex compounds of boric acid and polysaccharides (mannite, sorbitol, etc.), complex compounds of boric acid and polyhydric alcohols, boric acid esters, nitro compounds (o-nitrobenzoic acid, m-nitrobenzoic acid, p-nitrobenzoic acid, o-nitrophenol, m-nitrophenol, p-nitrophenol, p-nitrobenzyl alcohol, etc.), and phosphoric acid esters. These may be used alone or in combination of two or more. The amount of additive added is not particularly limited, but it is preferable to add additives to an extent that does not deteriorate the characteristics of the solid electrolytic capacitor 1, for example, 60 wt% or less in the liquid.

[0067] The capacitor element 2 on which the solid electrolyte is formed is housed in a cylindrical exterior case 16 with a bottom, and is sealed with a sealing body 17 made of an elastic material such as rubber. The material of the exterior case 16 can be an aluminum alloy containing aluminum, manganese, or the like, or stainless steel. The lead-out terminals 6-1, 6-2 are drawn out from the sealing body 17. The entire circumference of the open end of the exterior case 16 is crimped, completing the production of the solid electrolytic capacitor 1.

[0068] In this solid electrolytic capacitor 1, a thin oxide film of about 1 to 10 V may be formed on the surface of the cathode foil 4 by chemical conversion treatment, if necessary.

[0069] The separator 5 electrically isolates the anode foil 3 and the cathode foil 4 to prevent short circuiting, and also holds the solid electrolyte or the solid electrolyte and the electrolytic solution. If the solid electrolyte has high shape retention and can maintain its shape without a separator, the separator may be omitted.

[0070] (Action and effect) When a conductive polymer is present near the defect, the leakage current of the solid electrolytic capacitor 1 increases. On the other hand, when no conductive polymer is present near the defect, the leakage current of the solid electrolytic capacitor 1 is suppressed. Even if an electrolyte is present near the defect, the leakage current converges when no conductive polymer is present. Furthermore, even if a conductive polymer is present near the defect, the leakage current converges when an electrolyte is also present near the defect.

[0071] A conductive polymer dispersion 18 enters the gap 13-1 between the anode foil 3 and the lead terminal 6-1, which is generated by the stress when the anode foil 3 and the lead terminal 6-1 are connected and the restoring force of the anode foil 3 acting on the outer periphery of the capacitor element 2. The dielectric oxide film present in the gap 13-1 has a large defect due to contact with the lead terminal 6-1, and the conductive polymer adheres to the defect, which increases the leakage current. Furthermore, even if an electrolytic solution is present as an electrolyte, the size of the opening of the gap 13-1 is small, so that the electrolytic solution cannot enter the gap 13-1 when the conductive polymer adheres, making it difficult for the leakage current to converge.

[0072] In this solid electrolytic capacitor 1, coating layer 14 is formed on at least the portion of pull-out terminal 6-1 facing anode foil 3, which repels conductive polymer dispersion liquid 18 that attempts to penetrate into gap 13-1 formed between anode foil 3 and pull-out terminal 6-1, thereby suppressing the penetration of conductive polymer into at least gap 13-1. Therefore, there is less conductive polymer near the defect caused by the presence of pull-out terminal 6-1 compared to other portions of capacitor element 2.

[0073] Therefore, the leakage current of the solid electrolytic capacitor 1 is suppressed or converges.

[0074] From the above, it is sufficient to repel the conductive polymer forming solution attempting to enter the gap 13-1 between the anode foil 3 and the lead-out terminal 6-1, and the coating layer 14 may be formed on the surface of the anode foil 3. EXAMPLES

[0075] The solid electrolytic capacitor of the present invention will be described in detail below with reference to Figs. 8 and 9 based on examples. Fig. 8 is a diagram showing the position of coating layer 14 in Example 1, Fig. 8A is a plan view of anode foil 3 to which lead-out terminal 6-1 is connected, and Fig. 8B is a cc cross-sectional view of Fig. 8A. Fig. 9 is a diagram showing the position of coating layer 14 in Example 2, Fig. 9A is a plan view of anode foil 3 to which lead-out terminal 6-1 is connected, and Fig. 9B is a dd cross-sectional view of Fig. 9A. It should be noted that the present invention is not limited to the following examples.

[0076] Example 1 A solid electrolytic capacitor 1 of Example 1 was fabricated as follows. The anode foil 3 and the cathode foil 4 were strip-shaped aluminum foils stretched to a long length. The anode foil 3 was etched to enlarge its surface, and a dielectric oxide film was formed by chemical conversion treatment. The cathode foil 4 was a plain foil, i.e., not etched.

[0077] 8A and 8B, the flat plate portion 7 of the lead terminal 6-1 was immersed in a solution of a coating agent to form a coating layer 14 on the entire surface of the flat plate portion 7 of the lead terminal 6-1. The thickness of the coating layer 14 was set to 200 nm. The coating liquid used an organic solvent, a fluororesin containing an organic solvent obtained by mixing m-xylene hexafluoride, ethyl perfluoroisobutyl ether, and ethyl perfluorobutyl ether.

[0078] An extraction terminal 6-1 having a coating layer 14 formed thereon was attached to the anode foil 3 by stitch connection. The flat plate portion 7 of the extraction terminal 6-1 was aligned along one side of the anode foil 3 so as to be perpendicular to the long side of the anode foil 3, and the round bar portion 8 was aligned so as to protrude from one long side of the anode foil 3. An extraction terminal 6-2 was similarly connected to the cathode foil 4. The anode foil 3 and cathode foil 4 were placed opposite each other with a manila separator 5 interposed therebetween, and wound so that the long side was rounded, to form the capacitor element 2.

[0079] Capacitor element 2 was immersed in an aqueous solution of ammonium dihydrogen phosphate at 90° C. for 20 minutes, and during the immersion time, a current of 5 mA was passed through it with an applied voltage of 56.5 V. After the repair formation was completed, capacitor element 2 was left to stand in a temperature environment of 105° C. for 30 minutes and dried.

[0080] After drying, the capacitor element 2 was immersed in an aqueous solution of polystyrene sulfonic acid (PSS) and polyethylenedioxythiophene (PEDOT) dispersed in water for 120 seconds from the side opposite the lead terminal lead-out end surface 11 of the capacitor element 2 in a reduced pressure environment of 30 kPa. The capacitor element 2 was then left to stand for 30 minutes in a temperature environment of 150°C to dry. The immersion and drying were treated as a series of processes, and the series of processes was repeated twice. As a result, a solid electrolyte was formed in the capacitor element 2.

[0081] Next, an electrolyte solution was prepared by adding ammonium borodisalicylate to a 5% ethylene glycol solution, and the electrolyte was impregnated into the capacitor element 2 on which the solid electrolyte was formed. The wound capacitor element 2 thus produced, having a diameter of 6.1 mm and a height of 6.3 mm, was inserted into a cylindrical aluminum exterior case 16 with a bottom, and a sealing body 17 was attached to the open end and sealed by crimping. Then, a voltage was applied for 45 minutes in a temperature environment of 115°C, and the solid electrolytic capacitor 1 was subjected to an aging treatment.

[0082] Example 2 The solid electrolytic capacitor of Example 2 was fabricated as follows. As shown in Figures 9A and B, the coating layer 14 was formed only on the metal wire 9 side of the flat portion 7 of the lead terminal 6-1. Specifically, the location where the coating layer 14 was formed corresponds to the formation position of the connection portion 15-1 closest to the metal wire 9 of the connection portion 15 between the anode foil 3 and the lead terminal 6-1, among the portions of the lead terminal 6-1 that contact the anode foil 3, up to the end of the flat portion 7 on the metal wire 9 side. The rest was fabricated in the same manner and under the same conditions as the solid electrolytic capacitor 1 of Example 1.

[0083] Comparative Example 1 A solid electrolytic capacitor of Comparative Example 1 was produced as follows: It was produced in the same manner and under the same conditions as solid electrolytic capacitor 1 of Example 1, except that no coating layer was formed on the lead-out terminals.

[0084] (Leakage current test) Sixty solid electrolytic capacitors each of Example 1, Example 2, and Comparative Example 1 were produced, and the reflow process with a peak temperature of 260°C was repeated twice for each solid electrolytic capacitor, and the leakage current was measured. The leakage current was measured for 120 seconds from the start of application of a voltage of 35 V in a temperature environment of 20°C.

[0085] The average values ​​of the measurement results of the leakage current of the solid electrolytic capacitors of Example 1, Example 2 and Comparative Example 1 are shown in Table 1 below.

[0086] [Table 1]

[0087] As can be seen from a comparison of Table 1, the solid electrolytic capacitor of Comparative Example 1 had an increased leakage current after the test. On the other hand, the solid electrolytic capacitors 1 of Examples 1 and 2, on which the coating layer 14 was formed, did not show an increase in leakage current even after the test. It was also found that the coating layer 14 is effective when it is formed at a position corresponding to the connection portion 15-1 closest to the metal wire 9 of the connection portion 15 between the anode foil 3 and the draw-out terminal 6-1, among the portions of the draw-out terminal 6-1 that contact the anode foil 3, and the end of the flat portion 7 on the metal wire 9 side.

[0088] Example 3 Solid electrolytic capacitor 1 of Example 3 was fabricated as follows. Coating layer 14 formed on lead terminal 6-1 had a thickness of 100 nm. Otherwise, solid electrolytic capacitor 1 of Example 1 was fabricated in the same manner and under the same conditions.

[0089] Example 4 Solid electrolytic capacitor 1 of Example 4 was fabricated as follows. Coating layer 14 formed on lead terminal 6-1 had a thickness of 50 nm. Otherwise, solid electrolytic capacitor 1 of Example 1 was fabricated in the same manner and under the same conditions.

[0090] Example 5 Solid electrolytic capacitor 1 of Example 5 was fabricated as follows. Coating layer 14 formed on lead terminal 6-1 had a thickness of 40 nm. Otherwise, solid electrolytic capacitor 1 of Example 1 was fabricated in the same manner and under the same conditions.

[0091] Example 6 Solid electrolytic capacitor 1 of Example 6 was fabricated as follows. Coating layer 14 formed on lead-out terminal 6-1 had a thickness of 30 nm. Otherwise, solid electrolytic capacitor 1 of Example 1 was fabricated in the same manner and under the same conditions.

[0092] Example 7 Solid electrolytic capacitor 1 of Example 7 was fabricated as follows. Coating layer 14 formed on lead terminal 6-1 had a thickness of 20 nm. Otherwise, solid electrolytic capacitor 1 of Example 1 was fabricated in the same manner and under the same conditions.

[0093] Example 8 Solid electrolytic capacitor 1 of Example 8 was fabricated as follows. The thickness of coating layer 14 formed on lead-out terminal 6-1 was set to 10 nm. Otherwise, solid electrolytic capacitor 1 of Example 1 was fabricated in the same manner and under the same conditions.

[0094] Example 9 Solid electrolytic capacitor 1 of Example 9 was fabricated as follows. Coating layer 14 formed on lead terminal 6-1 had a thickness of 5.2 nm. Otherwise, solid electrolytic capacitor 1 of Example 1 was fabricated in the same manner and under the same conditions.

[0095] Example 10 Solid electrolytic capacitor 1 of Example 10 was fabricated as follows. Coating layer 14 formed on lead-out terminal 6-1 had a thickness of 1.5 nm. Otherwise, solid electrolytic capacitor 1 of Example 1 was fabricated in the same manner and under the same conditions.

[0096] (Leakage current test 2) The leakage current was measured for the solid electrolytic capacitors of Example 1, Example 3 to Example 10, and Comparative Example 1. The conditions for measuring the leakage current were the same as those in the leakage current test 1 performed for Example 1, Example 2, and Comparative Example 1.

[0097] (Wettability test) In addition, the wettability with the dispersion liquid for each thickness of the coating layer in Example 1, Example 3 to Example 10 was confirmed. The wettability was obtained by measuring the contact angle of the coating agent used in each Example and Comparative Example. Specifically, a coating layer having a thickness set in the above-mentioned Examples 1, 3 to 10 was formed on the surface of a plain aluminum foil that had not been subjected to a surface enlargement treatment such as etching or a treatment such as a dielectric oxide film formation treatment. Next, the dispersion liquid used in the above-mentioned Examples 1, 3 to 10, and Comparative Example 1 was dropped on the aluminum foil on which the coating layer was formed and the aluminum foil on which the coating layer was not formed, which corresponds to Comparative Example 1, and the contact angle between the dispersion liquid and the aluminum foil after 20 seconds was obtained by the Young-Lapace method.

[0098] The contact angles for each coating layer thickness set in Example 1, Examples 3 to 10, and Comparative Example 1, and the average values ​​of the measurement results of the leakage current of the solid electrolytic capacitors of Example 1, Examples 3 to 10, and Comparative Example 1 are shown in Table 2 below.

[0099] [Table 2]

[0100] As can be seen from a comparison of Table 2, Example 1 and Examples 3 to 10 in which the coating layer 14 is formed have smaller leakage currents and smaller rates of change after the test compared to Comparative Example 1 in which the coating layer 14 is not formed. This demonstrates that forming the coating layer 14 is effective in reducing leakage current. Furthermore, Example 1 and Examples 3 to 8 in which the coating layer 14 has a thickness of 10 nm or more have a significantly smaller rate of change compared to Examples 9 and 10 in which the coating layer 14 is 10 nm or less. Furthermore, Example 1 and Examples 3 to 7 in which the coating layer 14 has a thickness of 20 nm or more have leakage currents within 150% before and after the test, confirming a remarkable effect. Furthermore, when the contact angle of the coating layer 14 was also checked, it was confirmed that this was related to the reduction in leakage current. In other words, it was confirmed that by providing the coating layer 14 with a contact angle of 80° or more, the leakage current in the solid electrolytic capacitor 1 was minimized.

[0101] Next, in order to confirm the influence of the coating layer 14 on the connectivity with the anode foil 3, the contact resistance was measured.

[0102] Example 11 The solid electrolytic capacitor of Example 11 was produced as follows. Specifically, the thickness of the coating layer 14 formed on the lead-out terminal 6-1 was set to 200 nm, and otherwise the solid electrolytic capacitor was produced in the same manner and under the same conditions as the solid electrolytic capacitor 1 of Example 1.

[0103] Example 12 A solid electrolytic capacitor of Example 12 was produced as follows. It was produced in the same manner and under the same conditions as solid electrolytic capacitor 1 of Example 1, except that the thickness of coating layer 14 formed on lead-out terminal 6-1 was set to 150 nm.

[0104] Example 13 A solid electrolytic capacitor of Example 13 was produced as follows. It was produced in the same manner and under the same conditions as solid electrolytic capacitor 1 of Example 1, except that the thickness of coating layer 14 formed on lead-out terminal 6-1 was set to 100 nm.

[0105] Example 14 A solid electrolytic capacitor of Example 14 was produced as follows. It was produced in the same manner and under the same conditions as solid electrolytic capacitor 1 of Example 1, except that the thickness of coating layer 14 formed on lead-out terminal 6-1 was set to 80 nm.

[0106] Example 15 A solid electrolytic capacitor of Example 15 was produced as follows. It was produced in the same manner and under the same conditions as solid electrolytic capacitor 1 of Example 1, except that the thickness of coating layer 14 formed on lead-out terminal 6-1 was set to 60 nm.

[0107] (Example 16) A solid electrolytic capacitor of Example 16 was produced as follows. It was produced in the same manner and under the same conditions as solid electrolytic capacitor 1 of Example 1, except that the thickness of coating layer 14 formed on lead-out terminal 6-1 was set to 50 nm.

[0108] (Example 17) A solid electrolytic capacitor of Example 17 was produced as follows. It was produced in the same manner and under the same conditions as solid electrolytic capacitor 1 of Example 1, except that the thickness of coating layer 14 formed on lead-out terminal 6-1 was set to 40 nm.

[0109] (Example 18) The solid electrolytic capacitor of Example 18 was produced as follows. It was produced in the same manner and under the same conditions as the solid electrolytic capacitor 1 of Example 1, except that the thickness of the coating layer 14 formed on the lead-out terminal 6-1 was set to 30 nm.

[0110] (Example 19) A solid electrolytic capacitor of Example 19 was produced as follows. It was produced in the same manner and under the same conditions as solid electrolytic capacitor 1 of Example 1, except that the thickness of coating layer 14 formed on lead-out terminal 6-1 was set to 20 nm.

[0111] (Example 20) A solid electrolytic capacitor of Example 20 was produced as follows. It was produced in the same manner and under the same conditions as solid electrolytic capacitor 1 of Example 1, except that the thickness of coating layer 14 formed on lead-out terminal 6-1 was set to 10 nm.

[0112] Example 21 A solid electrolytic capacitor of Example 21 was produced as follows. It was produced in the same manner and under the same conditions as solid electrolytic capacitor 1 of Example 1, except that the thickness of coating layer 14 formed on lead-out terminal 6-1 was set to 5.2 nm.

[0113] Example 22 A solid electrolytic capacitor of Example 18 was produced as follows. It was produced in the same manner and under the same conditions as solid electrolytic capacitor 1 of Example 1, except that the thickness of coating layer 14 formed on lead-out terminal 6-1 was set to 1.5 nm.

[0114] Comparative Example 2 A solid electrolytic capacitor of Comparative Example 2 was produced as follows. The lead terminal 6-1 was produced in the same manner and under the same conditions as the solid electrolytic capacitor 1 of Example 1, except that the coating layer 14 was not formed on the lead terminal 6-1.

[0115] (Contact resistance test) The contact resistance between the anode foil 3 and the lead terminal 6-1 of Examples 11 to 22 and Comparative Example 2 was measured. Specifically, ten solid electrolytic capacitors were prepared for each of Examples 11 to 22 and Comparative Example 2, and five of the ten were subjected to a reflow process with a peak temperature of 260°C twice. Thereafter, the ten solid electrolytic capacitors were disassembled, the anode foil 3 connected to the lead terminal 6-1 was removed, and each electrode terminal of a resistance meter was connected to the round bar portion 8 of the lead terminal 6-1 and the anode foil 3. Then, while maintaining the position of the anode foil 3, the lead terminal 6-1 was lifted by 0.8 mm, and the contact resistance was measured. A model RM3545 manufactured by Hioki E.E. Corporation was used as the resistance meter. The measurement results show the total value of the resistance value of the anode foil 3, the resistance value of the lead terminal 6-1, and the connection resistance. The resistance values ​​of the anode foil 3 and the lead-out terminal 6-1 are the same in Examples 11 to 22 and Comparative Example 2 because the anode foils 3 and lead-out terminals 6-1 used in each Example and Comparative Example are the same.

[0116] The results of this contact resistance test are shown in Table 3. The contact resistance value is the average value of five pieces.

[0117] [Table 3]

[0118] Since the anode foil 3 and the lead terminal 6-1 in Examples 11 to 22 and Comparative Example 2 are the same, the resistance value of the anode foil 3 and the resistance value of the lead terminal 6-1 are the same in Examples 11 to 22 and Comparative Example 2. Therefore, the difference in the measurement results shown in Table 3 is the difference in the contact resistance between the anode foil 3 and the lead terminal 6-1. As shown in Table 3, in Examples 12 to 22, the increase in the contact resistance after the test can be suppressed to 1.5 times. From this, it is recognized that the increase in the contact resistance can be suppressed by setting the thickness of the coating layer 14 to 150 nm or less. That is, it was confirmed that by setting the thickness of the coating layer 14 to 150 nm or less, even if the coating layer 14 is interposed in the connection part between the anode foil 3 and the lead terminal 6-1, the connectivity between the anode foil 3 and the lead terminal 6-1 is maintained and the contact resistance is low. It is presumed that this is due to the coating layer 14 having insulating properties, which inhibits the electrical connectivity between the anode foil 3 and the lead terminal 6-1. Furthermore, for Examples 14 to 22, the increase in contact resistance after the test can be suppressed to less than 1.1 times. That is, it was confirmed that the effect of suppressing the increase in contact resistance is remarkable by making the thickness of the coating layer 14 80 nm or less. This is thought to be because, by making the thickness of the coating layer 14 80 nm or less, when the cut-and-raised piece is pressed and connected to the anode foil 3 during stitch connection, the cut-and-raised piece stretches, and the coating layer 14 formed on the surface of the cut-and-raised piece 23 becomes thin enough that it does not affect the connectivity, or the base metal of the cut-and-raised piece 23 is exposed, improving the connectivity with the anode foil.

[0119] From the above, it was found that by setting the thickness of the coating layer 14 to 80 to 10 nm, a solid electrolytic capacitor 1 with low leakage current and low resistance could be obtained. [Explanation of symbols]

[0120] 1. Solid electrolytic capacitor 2. Capacitor elements 3 Anode foil 4 Cathode foil 5. Separator 6-1 Output terminal (anode side) 6-1 Lead terminal (cathode side) 7 Flat plate part 8 Round bar section 9 Metal Wire 10 hole 11 Output terminal lead-out end surface 12 Hole 13-1, 13-2 void area 14 Coating Layer 15-1, 15-2 Connection 16 Outer case 17 Sealing body 18 Dispersion 19 Lower mold 20 Through hole 21 Upper mold 22 Stitching Needles 23 Cut-out piece 24 Molding mold

Claims

1. an anode foil having a dielectric oxide film formed thereon; A lead terminal connected to the anode foil; A capacitor element including the anode foil; A solid electrolyte including a conductive polymer is formed in the capacitor element, forming a coating layer between the anode foil and the lead-out terminal that repels a conductive polymer forming solution; A solid electrolytic capacitor, characterized in that the thickness of the coating layer is 10 nm or more and 150 nm or less.

2. 2. The solid electrolytic capacitor according to claim 1, wherein the coating layer has a thickness of 10 nm to 100 nm.

3. 3. The solid electrolytic capacitor according to claim 1, wherein the coating layer has a thickness of 10 nm to 80 nm.

4. 3. The solid electrolytic capacitor according to claim 1, wherein the coating layer is formed on at least a portion of the lead terminal that faces the anode foil.

5. 3. The solid electrolytic capacitor according to claim 1, wherein the coating layer is formed at least on a side of the lead terminal leading end face of the capacitor element from a connection portion of the lead terminal with the anode foil.

6. 4. The solid electrolytic capacitor according to claim 1, wherein a contact angle between the surface of said coating layer and said conductive polymer forming solution is 80[deg.] or more.

7. a winding step of connecting a lead terminal to the cathode foil and the anode foil on which the dielectric oxide film is formed, and then winding the cathode foil and the anode foil while rolling up the lead terminal to form a capacitor element; and an electrolyte forming step of immersing a surface of the capacitor element opposite to an end surface of the capacitor element from which the lead-out terminal connected to the anode foil is led out, into a solution for forming a solid electrolyte, after the winding step, A method for manufacturing a solid electrolytic capacitor, comprising forming a coating layer having a thickness of 10 nm to 150 nm and repelling a conductive polymer forming solution at least between the anode foil and an anode-side extraction terminal.

Citation Information

Patent Citations

  • Lead wire for capacitor, solid electrolytic capacitor, and manufacturing method therefor

    JP2002083738A

  • Electrolytic capacitor

    JP2006114540A

  • Electrolytic capacitor

    JP2016122741A

  • Electrolytic capacitor

    JP2019201109A